An Analysis Of English Text Book For Elementary Grade Four - Lakcyta, Faradithya Putri (Jurnal Ilmiah Wahana Pendidikan, 2023)
The textbook is the most important thing in the school learning process. With the teacher's textbooks, it has more ways of delivering materials in the classroom as well as instruction while he is teaching. Similarly, the students were also greatly helped by the textbook, where they could read it whenever they wanted, and from there they could train their knowledge from the problems it contained. However, while the textbook has many benefits, there are times when there are many more in the book that the institution of education sets, so an evaluation of the textbook must also be done to prevent students from receiving incorrect or incorrect material. So this study aims to evaluate and synthesize a class 4 textbook with material (wake up! Alarm clock) by reference to the book the 2013 text completion and worthiness.